2019
DOI: 10.1021/acs.est.9b02116
|View full text |Cite
|
Sign up to set email alerts
|

Congener-Specific Mother–Fetus Distribution, Placental Retention, and Transport of C10–13 and C14–17 Chlorinated Paraffins in Pregnant Women

Abstract: Short-chain chlorinated paraffins (SCCPs) and medium-chain chlorinated paraffins (MCCPs) are high production volume persistent and toxic industrial chemicals, found ubiquitously in various environmental matrices. However, information is scarce regarding human internal exposure. The congener-specific SCCP and MCCP levels in matched maternal serum (n= 31), umbilical cord serum (n= 31), and placenta (n= 31) were studied to investigate the maternal-placenta-fetus distribution and the placental transport mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…Human serum Liu et al (2020b) reported ∑SCCP concentration in maternal and placenta human serum samples of about 117.1 ng mL −1 and 70.0 ng mL −1 , respectively, which were in the same range with those reported by Aamir et al (2019) and Qiao et al (2018). Ding et al (2020) also determined SCCP concentration in serum samples of about 107 ng g −1 ww, which were comparable with those previously reported in blood samples (Qiao et al 2018).…”
Section: Breast Milksupporting
confidence: 85%
See 1 more Smart Citation
“…Human serum Liu et al (2020b) reported ∑SCCP concentration in maternal and placenta human serum samples of about 117.1 ng mL −1 and 70.0 ng mL −1 , respectively, which were in the same range with those reported by Aamir et al (2019) and Qiao et al (2018). Ding et al (2020) also determined SCCP concentration in serum samples of about 107 ng g −1 ww, which were comparable with those previously reported in blood samples (Qiao et al 2018).…”
Section: Breast Milksupporting
confidence: 85%
“…According to Xia et al (2017b), there is a concern about the presence of environmental pollutants in human breast milk because the pollutants could negatively affect the health of breastfeeding infants. In pregnant women, SCCPs normally accumulate in their blood and milk and then transmit to their foetus through either placental transfer or breastfeeding transfer (Aamir et al 2019;Yang et al 2018;Lyche et al 2015). Due to their immature metabolism, infants are more vulnerable than older humans to potentially harmful chemicals (Darnerud et al 2001).…”
Section: Humansmentioning
confidence: 99%
“…2,4−7 Studies have shown that SCCPs could be detected in various environmental and human samples, including air, 8,9 dust, 10,11 soil, 12,13 sluge, 14,15 biota, 16−18 human blood, 19 breast milk, and maternal and cord serum. 20,21 Since SCCPs have been listed in Annex A of the Stockholm Convention in 2017, 22 the production and usage of MCCPs as replacement chemicals is increasing. The total registered volume of MCCPs production in Europe was about 10000−100000 t/year, much higher than that of SCCPs (1000−10000 t/year).…”
Section: Introductionmentioning
confidence: 99%
“…1 MCCPs and LCCPs are also of environmental concern because of their frequent detection in various environmental and biological samples [2][3][4][5] including samples from humans. 6,7 Environmental property values such as equilibrium partition coefficients (K) need to be known for environmental fate and risk assessments, although the extremely high complexity of CP mixtures hampers the use of conventional experimental and theoretical approaches to obtain their property data.…”
Section: Introductionmentioning
confidence: 99%